Timmy Understands Refraction - Bao, Dongni; Hong, Jun; Tan, Boon Hui; Wan-Lau, Ruth, 1976- (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2021)
A family fishing trip turns out to be full of learning fun for Timmy. Watch how he discovers facts about refraction, and becomes an expert that advises others too!
First published in China by China Children's Press and Publication Group Co., Ltd.
An Augmented Reality Experience.
Translated from the Chinese.
Keywords: Chinese -- Juvenile literature -- Translations into English; Refraction -- Juvenile literature; Light -- Juvenile literature